ANALISIS BANTUAN LCD INTERACTIVE WHITEBOARD UNTUK MENINGKATKAN PEMBELAJARAN PADA PAUD HIBER KOTA BANDUNG - Sari, Rianti Garvita; Yoseptry, Ricky; Hendarsyah, Jelita Dewanty; Dalina, Lina (STKIP PGRI Situbondo, 2024)
This research is motivated by the development of Technology in the world of education, which with this development has become a challenge for the world of education, especially PAUD Hiber so that it can provide interesting, fun, interactive, and varied learning through the demands of the times in the digital era. Currently, many non-formal education institutions have emerged that have quite modern infrastructure, therefore this is a warning for formal early childhood education institutions to carry out various innovations in learning so that they can compete with non-formal institutions. In connection with this learning media being an important element in supporting the learning process in a varied, creative, and innovative way, to improve learning at Hiber PAUD in Bandung City, it is necessary to have facilities that support improving the quality of learning, so by providing this cinematic assistance it is hoped that it can be used to support the learning of young children. early so that learning is more interesting and interactive. This research aims to describe the strengths, weaknesses, opportunities, and threats of the Liquid Crystal Display Interactive Whiteboard cinematic assistance. The research location was carried out by the Bandung City Education Office, TK Assalam, and Kober Imanda. Using qualitative descriptive research methods. This research concludes that we can obtain an overview of the assistance of the Liquid Crystal Display (LCD) Interactive Whiteboard cinematic obtained through SWOT analysis.